Organizing Halal Certification Services After Law No 6 Cipta Kerja 2023 Case Study Halal Center Uin Sunan Kalijaga - Warsis Mawardi; Muchammad Ichsan; Moh. Lubsi Tuqo Romadhan (Faculty of Law, Universitas Pekalongan, 2024)
Law Number 06 of 2023 concerning Halal Product Guarantee is one of the laws included in the structuring cluster of the Law on Job Creation (omnibus law). Several provisions / norms were changed as an effort to regulate regulations for the ease of business licenses in Indonesia, Halal certification for MSE Products, changes in the authority to accredit the Halal Examining Agency (LPH), the authority to certify Halal Auditors, the involvement of Islamic organizations in the implementation of LPH, simplifying the bureaucracy, the timing of issuing Halal certificates and changing sanctions for norm violations are some of the provisions that distinguish between the Law on Halal Product Guarantee and the Law on Job Creation in this Halal Product Guarantee (JPH) cluster. This method was chosen because the analysis cannot be in the form of numbers and researchers describe all phenomena that exist in society clearly. This research also contains facts that occur in the field and an overview of the role of the Halal Center UIN Sunan Kalijaga in carrying out the mandate of the Job Creation Law on Halal Product Guarantee so that it can then be studied in depth with theoretical approaches. LP3H UIN Sunan Kalijaga has conducted 6 batches of PPH Facilitator Training, from March - July 2022 and from around 1400 participants only graduated 900 PPH Facilitators from all over Indonesia. In 2023, LP3H UIN Sunan Kalijaga began to hold PPH Facilitator Training, as of July 2023 it has conducted up to 12 batches of training, and from 2200 participants graduated 1400 PPH Facilitators from all over Indonesia. The cost comparison after the existence of the Job Creation Law is quite significant where previously they had to pay a minimum of Rp. 2,500,000, - while now it is only 0 rupiah or free